5- ‘Increasing my value proposition to the struggle’: Arthur Mutambara and student politics in Zimbabwe - Zeilig, Leo (African Sociological Review, 2006)
Arthur Mutambara made a dramatic return to Zimbabwean politics in 2005, to lead one of the factions of the split opposition, the Movement for Democratic Change. He was a prominent student activist in Zimbabwe in the late 1980s, and his reputation rests on this legacy. Mutambara led the Student Representative Council (SRC) as General Secretary and then as President at the University of Zimbabwe (UZ) from 1988-1990. This period has been eulogised by the students, civil society activists and trade unionists in Zimbabwe ever since. Students still refer affectionately to the period as the ‘AGO era’ – as he used to sign himself in the 1980s. Many have argued that the student movement became the seed bed for an emergent civil society. By 1990 Zimbabwe was permanently changed and ZANU-PF became the sullied party of liberation. Students helped to pierce the regime’s invulnerability, and other groups emerged to voice their own grievances. This paper uses the re-entry of Mutambara into Zimbabwean politics to examine the trajectory of the student movement, a subject that has received no attention in recent discussion of Zimbabwe’s political history.